KONTRIBUSI KOMPENSASI DAN MOTIF BERPRESTASI TERHADAP ETOS KERJA GURU PENJAS ORKES:Studi Analitik terhadap Guru Pendidikan Jasmani Olahraga dan Kesehatan SD di Kecamatan Darmaraja Kabupaten Sumedang - Supriadi, Cecep (2012)
The study was based on the tendency of less optimal work ethic Physical Education teacher. The purpose of this study to determine the effect of compensation and achievement motives of teachers Penjas work ethic. Hypothesis. First, compensation provides a significant contribution to physical education teachers work ethic. Second, the motive of achieving a significant contribution to the work ethic of physical education teachers. Third, compensation and achievement motives together exhibited significantly contribute to the physical education teachers work ethic. This study uses descriptive quantitative study of inferential statistics. Data were collected from 33 respondents specified. Data on the analysis of correlation and regression techniques on a 95% confidence tarap or ^0; = 0.05. The results support the hypothesis, granting compensation to contribute significantly to the work ethic of Physical Education teachers at 21.2%. Achievement motive contributes significantly to the work ethic of physical education teachers at 52.7%. Compensation and achievement are the same motif contributes significantly to the work ethic of Physical Education teachers at 54.5%. Based on the findings of the study recommended several things, including the compensation awarded should be reviewed in order to adapt to the development of price increases, the needs of teachers and their families, to enhance the achievement motive in addition to compensation received will also need to provide an opportunity for physical education teachers to develop skills and creativity in implementing managed learning and development of various parties, thus allowing physical education teacher performance is achieved the better.